2013
DOI: 10.2337/dc12-1489
|View full text |Cite
|
Sign up to set email alerts
|

Acute Macrovascular Dysfunction in Patients With Type 2 Diabetes Induced by Ingestion of Advanced Glycated β-Lactoglobulins

Abstract: OBJECTIVERecent evidence indicates that heat-enhanced food advanced glycation end products (AGEs) adversely affect vascular function. The aim of this study was to examine the acute effects of an oral load of heat-treated, AGE-modified β-lactoglobulins (AGE-BLG) compared with heat-treated, nonglycated BLG (C-BLG) on vascular function in patients with type 2 diabetes mellitus (T2DM).RESEARCH DESIGN AND METHODSIn a double-blind, controlled, randomized, crossover study, 19 patients with T2DM received, on two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…Ten parallel 17 , 19 29 and seven randomised crossover studies 10 , 16 , 18 , 22 , 30 37 were included. The studies were conducted at research centres 10 , 15 , 16 , 18 , 24 , 27 , 34 37 , hospitals 20 , 28 , 30 , 32 , 33 and universities 17 , 19 , 21 23 , 25 , 26 , 29 , 31 in USA 17 , 20 24 , 27 29 , Australia 16 , 18 , Denmark 19 , 31 , Germany 10 , 34 37 , Mexico 25 , 26 , Spain 30 , 32 , 33 and France 15 . Twelve studies involved people without T2DM 15 , 17 , 18 , 21 , 23 , 26 33 , and six were in patients with T2DM 10 , 17 , 22 , 24 , 25 , 34 37 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten parallel 17 , 19 29 and seven randomised crossover studies 10 , 16 , 18 , 22 , 30 37 were included. The studies were conducted at research centres 10 , 15 , 16 , 18 , 24 , 27 , 34 37 , hospitals 20 , 28 , 30 , 32 , 33 and universities 17 , 19 , 21 23 , 25 , 26 , 29 , 31 in USA 17 , 20 24 , 27 29 , Australia 16 , 18 , Denmark 19 , 31 , Germany 10 , 34 37 , Mexico 25 , 26 , Spain 30 , 32 , 33 and France 15 . Twelve studies involved people without T2DM 15 , 17 , 18 , 21 , 23 , 26 33 , and six were in patients with T2DM 10 , 17 , 22 , 24 , 25 , 34 37 .…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted at research centres 10 , 15 , 16 , 18 , 24 , 27 , 34 37 , hospitals 20 , 28 , 30 , 32 , 33 and universities 17 , 19 , 21 23 , 25 , 26 , 29 , 31 in USA 17 , 20 24 , 27 29 , Australia 16 , 18 , Denmark 19 , 31 , Germany 10 , 34 37 , Mexico 25 , 26 , Spain 30 , 32 , 33 and France 15 . Twelve studies involved people without T2DM 15 , 17 , 18 , 21 , 23 , 26 33 , and six were in patients with T2DM 10 , 17 , 22 , 24 , 25 , 34 37 . The majority (n = 13) of the studies used high AGE diets which were two or more times higher in AGE content than the low AGE diets 1 , 10 , 15 , 17 19 , 22 24 , 27 37 and the rest used high AGE diets that were less than two times higher in AGE content than the low AGE diets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeh, Yang, Pai, Wu, and Chen () administered methylglyoxal‐derived AGEs to mice for 16 wk and found that the treatment accelerated the accumulation of AGEs in the kidneys, increased the expression of inflammasome‐related proteins, and decreased the levels of nitric oxide synthase and nitric oxide. In patients with type 2 diabetes, oral administration of AGE‐modified β‐lactoglobulin significantly impaired macrovascular function and decreased nitric oxide bioavailability, although the effect was transient (Stirban et al., ). Many studies on AGEs have been heavily suggested to play a role in the progression of many age‐related and diabetic complications.…”
Section: Ages and Their Association With Diseasementioning
confidence: 99%
“…We therefore performed a randomized, double-blind, controlled, cross-over study that aimed at investigating the acute effects of dietary AGEs resulting from nonenzymatic glycation during heating of beta-lactoglobulins (a protein class frequently encountered in food) and compared these effects to nonglycated, but heated beta-lactoglobulins (BLG) [ 84 ]. Thus, the sole difference between the 2 protein preparations was the advanced protein glycation.…”
Section: Are the Above-mentioned Effects Due To Ages?mentioning
confidence: 99%